Effect of Comorbidity Assessed by the Charlson Comorbidity Index on the Length of Stay and Mortality Among Immobile Hemorrhagic Stroke Patients Younger Than 50 Years - Liu, Hongpeng; Wu, Xinjuan; Cao, Jing; Jiao, Jing; Zhu, Chen; Song, Baoyun; Jin, Jingfen; Liu, Yilan; Wen, Xianxiu; Cheng, Shouzhen (Frontiers in Neurology, 2020)
Objective: The burden of comorbidity among young patients with hemorrhagic stroke is high. This study examines the effect of comorbidity on the length of stay (LoS) and mortality among immobile hemorrhagic stroke patients younger than 50 years. Materials and Methods: A total of 767 younger adults (mean age 41.64±8.16 years) hospitalized for hemorrhagic stroke between November 2015 and July 2017 were evaluated. All-cause mortality was recorded for 90 days after admission regardless of whether death occurred before or after discharge. Comorbidity was assessed using the Charlson Comorbidity Index (CCI), categorized as low (0–1) and high (≥2). A multiple linear regression model was applied to examine the association between CCI and LoS. Survival was evaluated with Kaplan–Meier and Cox regression analyses. Results: Mean CCI of all patients was 1.25 (SD ±0.79) and median 1.0 (IQR 1, 1). The average LoS for patients with a low CCI was 17.73 (±11.59) days compared with 19.49 (±15.21) days in those with high CCI (p=.142). The mortality rate was 6.0% (12.10% for high CCI versus 4.82% for low CCI, p=.002). After controlling for confounders, high CCI was not associated with longer LoS (regression coefficient 0.825, 95% CI −1.155 to 2.805; p=.413), whereas high CCI was associated with greater likelihood of death than a low CCI (hazard ratio [HR] 3.417, 95% CI 1.626 to 7.180; p=.001). Conclusions: High global comorbidity was associated with increased short-term mortality but not with LoS. Measures to manage comorbidities aimed at reducing negative clinical impacts of stroke among younger adults are warranted.